Skeleton Key : [the graphic novel] - Horowitz, Anthony, 1955-; Damerum, Kanako; Johnston, Antony; Takasaki, Yuzuru (New York : Philomel Books, 2009)
On a routine mission at the Wimbledon tennis championships, reluctant teenage spy Alex Rider gets caught up in Chinese gangs, illegal nuclear weapons, and the suspect plans of his Russian host, General Sarov.
Subtitle from cover.
Keywords: Great Britain. -- MI6 -- Comic books, strips, etc; Spies -- Comic books, strips, etc; Teenagers -- Comic books, strips, etc; Graphic novels